2009
DOI: 10.1007/s00468-009-0404-2
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific variation and plasticity in growth and foliar morphology along a climate gradient in the Canary Island pine

Abstract: Foliar plasticity in response to ontogeny, location within the plant and environmental changes is widespread among long-lived organisms. To quantify the phenotypic variation in needle morphology and anatomy in response to a climate gradient, we compared contrasted populations of Pinus canariensis grown in five sites inside and outside the natural distribution area of the species. Most needle and growth traits were strongly affected by site. In general, site xericity increased the relative area of the dermal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 25 publications
5
14
0
Order By: Relevance
“…Adaptive patterns in anatomical traits related to water transport and conservation may arise in response to gradients of habitat water availability (e.g. López et al., ). In our study area, none of the sites was classified as arid although AI suggested that water deficits would be highest at Polish sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adaptive patterns in anatomical traits related to water transport and conservation may arise in response to gradients of habitat water availability (e.g. López et al., ). In our study area, none of the sites was classified as arid although AI suggested that water deficits would be highest at Polish sites.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have indeed revealed non-trivial intraspecific geographic variation in gross leaf structure (Fajardo & Piper, 2011;González-Zurdo et al, 2016;López, Climent, & Gil, 2010;Ogaya & Peñuelas, 2007). However, the underlying variation of specific anatomical traits has been examined less often.…”
mentioning
confidence: 99%
“…A more common finding has been a little consistent pattern in leaf trait plasticity, in species such as P. canariensis (López et al . ), Q. suber (Ramírez‐Valiente et al . ), Betula pendula (Meier & Leuschner ) and Populus davidiana (Zhang et al .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, evidence for plasticity has been found in low and mid rainfall plantings of Pinus canariensis and P. pinea (López et al . ; Mutke et al . ) and to a lesser extent Q. ilex (Gratani et al .…”
Section: Introductionmentioning
confidence: 99%
“…ex DC. (López, Climent & Gil, ), Olea cerasiformis Rivas‐Mart. & del Arco (García‐Verdugo et al ., ; García‐Verdugo, ) and Croton scouleri Hook.f.…”
Section: Discussionmentioning
confidence: 99%